Project completion report to design and develop a monitoring and control system for project undertaking - Socorro, Roberto (University of the Philippines Diliman, 2010)
Performance measurement has become a standard process for monitoring and controlling the progress for any projects whether it is for construction and infrastructure project, software development, industrial and others. It employs the fundamental measurement-based feedback principals to increase the probability that a project's actual performance matches its expected/planned performance. A project is delivered on time and within budget or, at least, that there is an early warning of looming disaster. This process is generally well-understood by project managers and reasonably well supported by commercially-available tools. This paper reviews the fundamentals of project management, performance measurement, estimation during the project planning process are incorporated into the forecasting and re-base lining processes to yield a more realistic time-range prediction of the project's cost and duration.